Development of Unit Cost Indices and Database for Water and Wastewater Pipelines Capital Works. Issue 2 (3rd May 2016) - Rehan, Rashid; Younis, Rizwan; Unger, Andre J. A.; Shapton, Brendan; Budimir, Filip; Knight, Mark A.
Abstract : The objective of this work is to develop a unit cost database and index for water and wastewater pipelines capital works, and estimate inflation in their construction cost. This was accomplished by analyzing tender summaries and progress certificates from the cities of Niagara Falls and Waterloo, Ontario, Canada, that span the period from 1980 to 2008, as well as using data from RS Means construction cost database. This work describes the source data, data preparation procedure, and development of unit cost database and indices. The process first involved developing scaling relationships between the cost of standard components and their sizes by regression analysis using data from tender summaries and the RS Means database. Next, unit costs of reference watermain and sanitary sewer projects and standard components are computed. Finally, a relational database is developed to store the data and to perform the unit cost analysis.